Antibacterial Activity of Bay Leaf (Syzygium polyanthum) Ethanol Extract on Escherichia coli Growth - Eliya Mursyida; Raissa Almira; Santi Widiasari; Olvaria Misfa (Sistem Informasi, 2021)
Acute diarrhea is liquid stool with a frequency of more than 3 times a day and lasts less than 14 days. One of the most common causes of acute diarrhea is Escherichia coli. Diarrhea caused by bacteria can be treated with the use of antibiotics, but the relatively high intensity of antibiotic use causes various health problems, especially bacterial resistance. Therefore, the search for antibacterial agents derived from natural ingredients was carried out as an alternative treatment. Bay leaf (Syzygium polyanthum) is one of the natural ingredients that has the potential as an antibacterial because it contains active compounds such as essential oils, flavonoids (quercetin), saponins, tannins, and alkaloids. This study aimed to analyze the antibacterial activity of the ethanolic extract of bay leaves on the growth of Escherichia coli. This research uses the dilution method which aims to determine the Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC). The results showed that the MIC value at a concentration of 200mg/ml and the MBC value at a concentration of 500mg/ml.